LE "CANTUS FIRMUS" D'HERBERT DE CHERBURY - Lagrée, Jacqueline (Revue des sciences philosophiques et théologiques, 1992)
La philosophie religieuse d'Herbert de Cherbury présente un naturalisme qui récuse moins la possibilité de la révélation que la nécessité des médiations, messianiques ou sacerdotales. La théorie de la vérité et des notions communes entend fonder la paix religieuse sur l'accord de tous les hommes de bon sens et de bonne volonté sur cinq articles, noyau essentiel de ce qui est nécessaire au salut. Ce credo minimum garantit aussi l'intercommunication des cultures et des expériences religieuses, des païens aux sauvages en passant par les musulmans, puisque ce cantus firmus donne lieu historiquement à des variations polyphoniques harmonieuses et pacifiques dont le Rousseau du Vicaire Savoyard gardera l'écho. The religious philosophy of Herbert of Cherbury displays a naturalism which rejects the necessity for mediation, either by Messiahs or priesthoods, and to a lesser degree rejects also the possibility of revelation. His theory of truth and common notions aims to found religious peace upon the acceptance, by all men of sound common sense, of five articles as the essential nucleus for salvation. This minimum creed, were it adopted alike by pagans and savages as by Moslems, would foster the intercommunication of religious cultures and experiences, for this cantus firmus gives rise historically to harmonious and pacific polyphonic variations, of which Rousseau in his "Vicaire savoyard" will retain an echo.